Language Learning Attitudes (LLA) And Cooperative Learning - Normazla Ahmad Mahir; Harison @ Hanisa Mohd Sidek (Universiti Sains Islam Malaysia, 2024)
This research conducted on the Quranic and Sunnah students at USIM studied the participants’ Language Learning Attitudes (LLA) in learning English as a second language using five personality traits as attitude indicators. It led to the findings that the participants were risk averse, low in self-image, low in tolerance of ambiguity, high in ego permeability and highly inhibited. One of the effective methods that can be used to nurture good attitudes as to enhance learning and acquisition is through the implementation of cooperative learning strategy. This strategy helps build learners’ confidence to take more risk in language learning as well as develop tolerance towards uncertainties in the learning process. Cooperative learning as the name suggests enables learners to work interdependently as to create learning network that provides appropriate language learning support to produce better LLA. To achieve this aim, ESL teachers ought to know how cooperative learning helps to mend learners’ LLA. In addition, they also need to know how it can be exploited to produce favourable learning attitudes in the classroom, which in the case of this study is to improve the abovementioned five learning personalities.